Paleoclimate Changes in the Pacific Northwest Over the Past 36, 000 Years From Clumped Isotope Measurements and Model Analysis. Issue 2 (7th February 2023) - Lopez‐Maldonado, Ricardo; Bateman, Jesse Bloom; Ellis, Andre; Bader, Nicholas E.; Ramirez, Pedro; Arnold, Alexandrea; Ajoku, Osinachi; Lee, Hung‐I; Jesmok, Gregory; Upadhyay, Deepshikha; Mitsunaga, Bryce; Elliott, Ben; et al.
Abstract: Since the last glacial period, North America has experienced dramatic changes in regional climate, including the collapse of ice sheets and changes in precipitation. We use clumped isotope (∆47 ) thermometry and carbonate δ 18 O measurements of glacial and deglacial pedogenic carbonates from the Palouse Loess to provide constraints on hydroclimate changes in the Pacific Northwest. We also employ analysis of climate model simulations to help us further provide constraints on the hydroclimate changes in the Pacific Northwest. The coldest clumped isotope soil temperatures T ( ∆ ${\increment}$ 47 ) (13.5 ± 1.9°C to 17.1 ± 1.7°C) occurred ∼34, 000–23, 000 years ago. Using a soil‐to‐air temperature transfer function, we estimate Last Glacial Maximum (LGM) mean annual air temperatures of ∼−5.5°C and warmest average monthly temperatures (i.e., mean summer air temperatures) of ∼4.4°C. These data indicate a regional warming of 16.4 ± 2.6°C from the LGM to the modern temperatures of 10.9°C, which was about 2.5–3 times the global average. Proxy data provide locality constraints on the boundary of the cooler anticyclone induced by LGM ice sheets, and the warmer cyclone in the Eastern Pacific Ocean. Climate model analysis suggests regional amplification of temperature anomalies is due to the proximal location of the study area to the Laurentide Ice Sheet margin and the impact of the glacial anticyclone on the region, as well as local albedo. Isotope‐enabled model experiments indicate variations in water δ 18 O largely reflect atmospheric circulation changes and enhanced rainout upstream that brings more depleted vapor to the region during the LGM. Plain Language Summary: Warming and water isotope variations inferred from clumped isotopes are similar to transient climate model simulations for the Pacific Northwest from the Last Glacial Maximum to present. The amount of warming was larger than the global average and is likely due to the proximity of the site to the glacial margin. Key Points: Clumped isotopes reveal changes in temperature and water isotopes over the past 36, 000 years consistent with transient model simulations Warming since the LGM was 16.4 ± 2.6°C, 2.5–3x the global average, likely due to proximity of site to ice margin Model analysis indicates δ 18 O depletion in this location at the LGM is largely a result of the North American ice sheets